Increasing Students’ Activity and Learning Outcome Used Guided Discovery Model Assisted by PhET - Siti Raihanah; Eko Susilowati; Abdul Salam (Berkala Ilmiah Pendidikan Fisika, 2019)
The purpose of this study is to increase student's activity and learning outcome using guided discovery assisted by PhET (Physics Education Technology). The specific purpose of this study is to describe: 1) the implementation of the lesson plan, 2) activity, and 3) learning outcomes. The type of study that used is a classroom action research by Kemmis and Mc Taggart model that consists of two cycles. The subject of this study is the 24 students of class XII one of the vocational schools in the Banjarmasin city. The data is obtained through observation and test. The results of study in cycles I and II show: 1) the average score of implementation of the lesson plan increased from good category to very good category, 2) the student’s activity has increased 3) the learning outcomes increased from 0% to 87.5% and has been declared complete in cycle II. It can be concluded that the used implementation of guided discovery with PhET can increase activity and learning outcomes.